Yield and Yield Attributing Characters of Promising Rice Genotypes under Dry Direct Seeded Conditions as Affected by Varieties and Weed Control Methods - Saphi, Dev Kumar; Yadav, Dil Raj; Yadav, Rajib Kumar; Yadav, Rajendra (International Journal of Applied Sciences and Biotechnology, 2018)
Dry direct seeded rice is an alternative to the farmers in the context of climate change and inputs scarcity especially labor. However, weeds are the major problem in dry direct seeded conditions competing with the different resources provided to the crop. Hence, field experiments were conducted for two consecutive years 2015 and 2016 in the experimental field of Rice Research Program, Hardinath, Dhanusha to identify the appropriate herbicides for DSR. The experiment was laid out in a split plot design and treatments were replicated thrice. Three varieties of rice namely Ciherang Sub-1, IET 16775 and Sukhkhadhan-3 were treated as main plot factors while five levels of weed control methods (Oxadiargyl @ 100 g a.i./ha as pre-emergence followed by Fenoxaprop @ 90 g a.i./ha with safener, Pendimethalin @ 1000 g a.i./ha as pre-emergence followed by Bispyribac sodium @ 25 g a.i/ha at three weeks after seeding, Pendimethalin @ 1000 g a.i./ha as pre-emergence followed by Pyrazosulfuron ethyl @ 25 g a.i.ha + Bispyribac sodium @ 25 g a.i./ha at three weeks after seeding, hand weeding and weedy check) were treated as sub-plot factors. The statistical analysis showed that the effect of weed control methods on yield and yield attributing parameters of the tested rice varieties was significant. Out of the tested treatments hand weeding yielded significantly higher grain yield (5.4 t/ha) followed by herbicides Pendimithalin fb Pyrazosulfuron ethyl + Bispyribac sodium; which reduced the weed density and was comparable with hand weeding. The interaction effect of weed control methods and varieties was found non-significant. Pendimithalin fb Pyrazosulfuron ethyl + Bispyribac sodium was found to control broad spectrum of weeds and also reduced the human labour drudgery and increasing the rice yield than the other herbicides in direct seeded rice.Int. J. Appl. Sci. Biotechnol. Vol 6(4): 313-318